KAJIAN NERACA AIR DI LAHAN GAMBUT PT. RIMBA HUTANI MAS - Lestari, Kunia; Junedi, Heri; Fuadi, Najla Anwar (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
Peatlands naturally function as water storage, water supply, and water controller. However, if they are not managed properly, this can cause changes in the water system or hydrology, especially fluctuations in groundwater levels. The decline in groundwater levels in peatlands triggers oxidation and subsidence, especially during the dry season. One effort that can be made to control this decline is to carry out a water balance analysis, which will provide a spatial and temporal understanding of the water's condition. This research was carried out in the Mangsang area at HTI PT. Rimba Hutani Mas, Merang District, Bayung Lencir District, Musi Banyuasin Regency, South Sumatra. The research was carried out by the survey method using the Thornthwaite & Mather Water Balance method. The data used included dimensions of drainage channels, rainfall, temperature, ground water level, and canal water level. The calculated data consisted of average monthly rainfall, average monthly air temperature, potential evapotranspiration, accumulated potential water loss, available water capacity, monthly differences in soil moisture storage, actual evapotranspiration, deficit, surplus, and direct runoff. The research results show that in the Mangsang area of ​​PT. Rimba Hutani Mas, there was a water surplus in March, April, November, and December and a deficit in January, February, May, June, July, August, September, and October. Although the calculation results indicate that water-deficit months occur in January, February, May, June, July, August, September, and October, this research area has been anticipated to avoid groundwater level fluctuations through effective water management and the construction of canal blocks.